Optimizing the National Health Economy: Utilizing Tobacco Excise to Improve Universal Health Coverage - Ni Luh Ayu Citra Mutiarahati; Luh Verra Sridyantari (Indonesian Journal of Global Health Research, 2024)
Tobacco Excise Tax (TET) plays a strategic role in increasing state revenue, which can be utilized to strengthen the National Health Insurance (NHI) system. This study aims to analyze the impact of raising tobacco excise taxes on the national health economy and the sustainability of health financing. A Systematic Literature Review (SLR) approach was employed, reviewing 20 journal articles published between 2018 and 2023. These articles were selected through a systematic process based on inclusion criteria such as topic relevance, applied methodology, and geographic focus.The findings reveal that increasing tobacco excise taxes is an effective strategy for enhancing public health and supporting economic development. Revenue from tobacco excise can serve as a sustainable source of funding for health initiatives, including addressing the JKN deficit, which amounted to IDR 31.7 trillion (USD 2.2 billion) as of May 2020. This funding shortfall, exacerbated by the COVID-19 pandemic, underscores the urgent need for alternative solutions. Additional revenue generated through increased tobacco taxes could be allocated to reduce the deficit and expand health service coverage.By raising excise tax rates, the government can simultaneously increase state revenue and encourage healthier behavior by reducing tobacco consumption. Thus, this policy has a dual role in improving public health indicators while strengthening the financial stability of NHI. A synthesis of the 20 reviewed articles indicates that such policies, if implemented consistently, could significantly reduce the JKN deficit and support the long-term sustainability of the national health system.